Особливост розвитку координаційних здібностей дітей молодшого шкільного віку з депривацією зору в процесі фізичного виховання = The features of development of coordination skills of primary school children with visual deprivation in the process of physical education - Savlyuk, Svitlana (Journal of Education, Health and Sport, 2017)
Savlyuk S. P. Особливост розвитку координаційних здібностей дітей молодшого шкільного віку з депривацією зору в процесі фізичного виховання = The features of development of coordination skills of primary school children with visual deprivation in the process of physical education. Journal of Education, Health and Sport. 2016;6(11):108-124. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164221 http://ojs.ukw.edu.pl/index.php/johs/article/view/3972 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 31.10.2016. The features of development of coordination skills of primary school children with visual deprivation in the process of physical education S.P. Savlyuk Національний університет фізичного виховання і спорту України, м. Київ National University of physical education and sport of Ukraine, Kyiv УДК [373.5.015.3 : 796.011.3] 617.75 ОСОБЛИВОСТ РОЗВИТКУ КООРДИНАЦІЙНИХ ЗДІБНОСТЕЙ ДІТЕЙ МОЛОДШОГО ШКІЛЬНОГО ВІКУ З ДЕПРИВАЦІЄЮ ЗОРУ В ПРОЦЕСІ ФІЗИЧНОГО ВИХОВАННЯ Савлюк С.П. Національний університет фізичного виховання і спорту України, м. Київ Анотації: Мета: дослідити розвиток фізичних якостей дітей молодшого шкільного віку з депривацією зору (ДЗ) спеціальної школи-інтернату в процесі фізичного виховання. Матеріал: у дослідженнях прийняли участь 135 молодших школярів 6-10 років із ДЗ та 186 практично здорових однолітків того ж віку. Результати: встановлено: результати тестів «Човниковий біг 4х9 м» і «Метання тенісного м’яча на віддаль провідною і непровідною рукою» дітей із ДЗ статистично значуще гірші, ніж результати цих тестів їх практично здорових однолітків (р<0,05); визначено: результати тесту на статичну рівновагу дітей із ДЗ статистично значуще відрізняються від результатів тесту їх практично здорових однолітків (р<0,001). Висновки: вивчення особливостей рухової підготовленості дітей із ДЗ засвідчує зниження усіх показників координаційних здібностей у порівнянні зі здоровими однолітками на 35-64 %. Ключові слова: фізичний, якість, депривація, зір, координація, здібність. Савлюк С.П. Особенности развития координационных способностей детей младшего школьного возраста с депривацией зрения в процессе физического воспитания. Аннотация. Цель: исследовать развитие физических качеств детей младшего школьного возраста с депривацией зрения (ДЗ) специальной школы-интерната в процессе физического воспитания. Материал: в исследованиях приняли участие 135 младших школьников 6-10 лет с ДЗ и 186 практически здоровых ровесников того же возраста. Результаты: установлено: результаты теста на статическое равновесие детей с ДЗ статистически значительно отличаются от результатов этого теста их практически здоровых ровесников (р<0,001); выявлено: результаты тестов «Метание теннисного мяча на расстояние» и «Челночный бег 4х9 м» детей с ДЗ статистически значительно худшие, чем результаты этих тестов у их практически здоровых ровесников (р<0,05). Выводы: изучение особенностей двигательной подготовленности детей с ДЗ свидетельствует о снижении всех показателей координационных способностей по сравнению со здоровыми ровесниками на 35-64%. Ключевые слова: физический, качество, депривация, зрение, координация, способность. S.P. Savlyuk. The features of development of coordination skills of primary school children with visual deprivation in the process of physical education. Annotation. Aim: explore the development of physical skills of primary school children with vision deprivation (VD) of the special boarding school in the process physical education. Material: The study involved 135 primary school children of 6-10 years with VD and 186 almost healthy peers of the same age. Results: found: the test results on static balance of children with VD are statistically significantly different from the test results of their almost healthy peers (p <0.001); set: the test results of "shuttle run 4x9 m" and "throwing a tennis ball on distance by top and conductive hand" of children with VD are statistically significantly worse than the results of these tests of their almost healthy peers (p <0.05). Conclusions: the study of the characteristics of motor fitness of children with VD confirms reduction of all parameters of coordination abilities compared with healthy peers on 35-64%. Keywords: physical, quality, deprivation, vision, coordination, capability.